A radicalização dos movimentos religiosos no norte da Nigéria: um exemplo da polarização da sociedade nigeriana? - Luciani, Joseph (Revista Videre, 2011)
The objective of this article is to analyze one of the aspects of the polarization process going on in the Nigerian society, and particularly in the Northern Region: the radicalization of religious movements. Nigeria occupies an important strategic position in the international system. Most populated country in Africa, playing a key role in peacekeeping on the continent and provided with large reserves of natural resources (oil and gas) kindling all appetites, Nigeria is an essential regional power. And yet, the interreligious and interethnic conflict in the Northern region constitutes a serious threat to the unity of the country and, more generally speaking, to the stability of the West African region. Thus it is important to explore some of the factors that lead to this seeming polarization which the latest presidential elections (April 2011) appears to demonstrate strongly.